Transformasi Dewan Direksi Perusahaan BUMN melalui Pendekatan Perilaku Akuntansi Guna Antisipasi Resesi Global - Ade Manggala Hardianto; Diah Permata Sari; Tevi Leviany (Jurnal Akuntansi, Keuangan, dan Manajemen, 2023)
The board of change directors who are too "easy to come and easy to go" can worsen the company's performance conditions and increase the risks faced by the company. Purpose: The purpose of this research is to provide recommendations on the transformation of the board of directors so as not to give the impression of being dislodged, and as a strategic step in dealing with the world recession. Methodology: Research was in state-owned company which published financial reports on the Jakarta Stock Exchange. We desain the quantitative correlation between independent and dependent variables with or not using variable control. The study also involved Nine financial ratios to reflect a broader range of corporate conditions. Results: The results are First, H1 is accepted that skill is correlated to Return on Asset and Fixed Asset Turnover. Secondly, H2 is accepted that tenure is not correlated to financial performance. Third, H3 the ratio of a board of independent directors is correlated to profit Margin, net profit margin and cash ratio. Originality of the research, this study provided an idea of a new board performance director to anticipate bankruptcy indications of firms characterized by ROA and Fixed Asset Turnover, profit margin, cash ratio and net profit margin. Limitation: This research was conducted from 2009-2016 at a state-owned company which published financial reports on the Jakarta Stock Exchange.